THE ROLE OF DISCIPLINE AND LOYALTY ON TAX VOLUNTEERS' WORK PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT THE TAX CENTER OF UNIVERSITY OF JEMBER - Galih Wicaksono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
Tax volunteer is one of the programs created by the Director General of Taxes in collaboration with tax centres in higher education, one of which is the Tax Center of the University of Jember. This study aims to analyze the effect of discipline, loyalty, and Organizational Citizenship Behavior (OCB) on work performance and the role of OCB as an intervening variable towards the effect of discipline and loyalty on work performance. Data were collected by distributing online and offline questionnaires, with the sample consisting of 60 tax volunteers at the Tax Center of the University of Jember. Data were analyzed using Partial Least Square software. The results showed that discipline had a significant positive effect on OCB but had no effect on work performance. Loyalty had a significant positive effect on OCB and work performance. OCB had a significant positive effect on work performance. However, OCB failed to intervene in the effect of discipline and loyalty on work performance. Results of this research indicated that the management of the tax volunteer at the University of Jember's tax centre must continuously increase the loyalty of its members in order to improve OCB and work performance. Keywords: discipline, loyalty, OCB, tax volunteer, work performance